2016
DOI: 10.1371/journal.pone.0164878
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Interaction of Fe Nanoparticles with Lysozyme by Biophysical and Molecular Docking Studies

Abstract: Herein, the interaction of hen egg white lysozyme (HEWL) with iron nanoparticle (Fe NP) was investigated by spectroscopic and docking studies. The zeta potential analysis revealed that addition of Fe NP (6.45±1.03 mV) to HEWL (8.57±0.54 mV) can cause to greater charge distribution of nanoparticle-protein system (17.33±1.84 mV). In addition, dynamic light scattering (DLS) study revealed that addition of Fe NP (92.95±6.11 nm) to HEWL (2.68±0.37 nm) increases suspension potential of protein/nanoparticle system (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 37 publications
5
35
0
1
Order By: Relevance
“…48,52,75,82,83 Besides, the more negative zeta potential value for AuNPs@CALB suggests superior stability in relation to SA CALB/AuNPs, since the increase of repulsive forces reduces the tendency of colloidal aggregation. 77 The zeta potential experiments confirmed that CALB adsorption took place on AuNPs surfaces for both AuNPs@CALB and SA CALB/AuNPs. 84 The adsorption was also confirmed by SDS page (Figure S2, SI section).…”
Section: Probing the Aunps/calb Interactions At Macromolecular And Comentioning
confidence: 74%
See 1 more Smart Citation
“…48,52,75,82,83 Besides, the more negative zeta potential value for AuNPs@CALB suggests superior stability in relation to SA CALB/AuNPs, since the increase of repulsive forces reduces the tendency of colloidal aggregation. 77 The zeta potential experiments confirmed that CALB adsorption took place on AuNPs surfaces for both AuNPs@CALB and SA CALB/AuNPs. 84 The adsorption was also confirmed by SDS page (Figure S2, SI section).…”
Section: Probing the Aunps/calb Interactions At Macromolecular And Comentioning
confidence: 74%
“…76 The zeta potential (ζ) determination is a suitable technique for the assessment of the colloidal stability which plays a central role in the in vivo application of this system. 77 The ζ of citrate-stabilized AuNPs was −48.4 ± 2.6 mV. This value is indicative of the high stability of the particles.…”
Section: Probing the Aunps/calb Interactions At Macromolecular And Comentioning
confidence: 88%
“…Therefore, it is important to determine the relationship between chemical functionalities of NPs and their biological activities, for example, in NP-induced targeted drug delivery systems and medicinal applications [187]. Additionally, NPs can destabilize the structure of adsorbed proteins and vice versa, and subsequently change the function of proteins and colloidal stability of NPs [188].…”
Section: Opportunities and Challengesmentioning
confidence: 99%
“…Thec ontrolled adsorption of specific proteins from biological media is still in its infancy,a nd the findings discussed above clearly indicate the importance of proteins at interfaces and their crucial roles in dictating cellular uptake.I no rder to exert greater control over the interfaces and subsequent nanocarrier properties,t he interaction between proteins and nanoparticle surfaces can be predefined by design through controlled protein adsorption. Va rious nanoparticles such as metals, [151] semiconductors, [152] or nanodiamonds [153] have been stabilized by this emerging and versatile protein passivation strategy to enable in vitro and in vivo bioapplications.T here are different ways to add the desired proteins as stable bioadhesives to the nanoparticles, for example,t hrough electrostatic interactions, [154] non-covalent interactions, [155] or ligand-metal interactions. [152] As proteins offer multiple carboxylic acid, amino,a nd thiol/ disulfide groups,l igand exchange of weakly bound nanoparticle surface groups by the desired protein represents am ethod of choice to passivate,f or example,q uantum dots.…”
Section: Protein Bioadhesives Stabilize Nanoparticle Sensorsmentioning
confidence: 99%